Serum Proteomics Reveals Alterations in Protease Activity, Axon Guidance, and Visual Phototransduction Pathways in Infants With In Utero Exposure to Zika Virus Without Congenital Zika Syndrome - Macedo-da-Silva, Janaina; Rosa-Fernandes, Lívia; Barbosa, Raquel Hora; Angeli, Claudia B.; Carvalho, Fabiana Rabe; de Oliveira Vianna, Renata Artimos; Carvalho, Paulo C.; Larsen, Martin R.; Cardoso, Claudete Araújo; Palmisano, Giuseppe (Frontiers in Cellular and Infection Microbiology, 2020)
In 2015, ZIKV infection attracted international attention during an epidemic in the Americas, when neurological disorders were reported in infants who had their mothers exposed to ZIKV during pregnancy. World Health Organization (WHO) epidemiological data show that 5 to 15% of neonates exposed to ZIKV in the uterus have complications included in abnormalities related to Congenital Zika Syndrome (CZS). The risk of complications after birth is not well documented, however, clinical evidence shows that 6% of infants exposed to ZIKV during pregnancy have complications present at birth, and this rate rises to 14% when medical monitoring is performed in all exposed infants, regardless of birth condition. Thus, the evaluation and monitoring of all exposed infants are of foremost importance as the development of late complications has been increasingly supported by clinical evidence. The identification of changes in protein profile of infants exposed to ZIKV without CZS could provide valuable findings to better understand molecular changes in this cohort. Here, we use a shotgun-proteomics approach to investigate alterations in the serum of infants without CZS symptoms but exposed to intrauterine ZIKV (ZIKV) compared to unexposed controls (CTRL). A complex pattern of differentially expressed proteins was identified, highlighting the dysregulation of proteins involved in axon orientation, visual phototransduction, and global protease activity in children exposed to ZIKV without CZS. These data support the importance of monitoring children exposed to ZIKV during gestation and without early CZS symptoms. Our study is the first to assess molecular evidence of possible late disorders in children victims of the ZIKV outbreak in the Americas. We emphasize the importance of medical monitoring of symptomatic and asymptomatic children, as apparently unexplained late neurological and eye disorders may be due to intrauterine ZIKV exposure.